Knowledge Test Development for Dairy Farmers To Measure Knowledge Level About Scientific Dairy Farming Practices - Jena, Anupama; Chander, Mahesh; Sinha, Sushil K (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
In the present study, a test was developed to measure the knowledge level of dairy farmers about scientific dairy farming. A preliminary  set of 87 knowledge items was initially administered to 60 randomly selected dairy farmers for item analysis. The difficulty index and  discrimination index was found out, and the items with difficulty index ranging from 30 to 80 and the discrimination index ranging from  0.30 to 0.55 were included in the final format of the knowledge test. A total of 48 items which fulfilled both the criteria were selected  for the final format of knowledge test. Reliability of the test through split half method was found out to be 0.386 and the coefficient of  correlation value by the test-retest method was 0.452, which was found to be significant at 1% level of significance. Hence, the knowledge  test constructed was highly stable, reliable and validated for measuring what it intends to.
Keywords: Knowledge; Scientific dairy farming; Test